Factors affecting breastfeeding practices among working mothers in Kuala Langat district / Siti Harirotul Hamrok Asis - Siti Harirotul, Hamrok Asis (2017)
The aims of this study were to determine the factors associated with breastfeeding duration including employment factors and the provision of employer support for breastfeeding among working mothers at workplace as well as the facilitating factors for working mothers to sustain exclusive breastfeeding practice. A cross sectional study involving 964 mothers with six months old babies was carried out from 1st February to 31st December, 2010. Face to face interview using a validated pretested structured questionnaires wasnconducted to assess sociodemographic factors, maternal characteristics, infant characteristics, cultural belief characteristic, knowledge, attitude and practice on breastfeeding, employment characteristics, worksite breastfeeding education, breastfeeding policy, facilities available in workplace and breastfeeding practice at six months. Univariate and multivariate analysis were used to determine the factors affecting the breastfeeding practice for six months duration. A qualitative study using purposive sampling from participants involved in an earlier study who expressed breastmilk during working and were exclusively or predominantly breastfeeding their infants up to 4 months were followed-up. The sampling method was theoretical sampling and the data collection technique was by in depth interview. The interviews were audio taped and transcribed verbatim.The transcribed data were analysed via thematic analysis. The sampling was continued until data saturation was met, which in this study was up to 15 participants. Cross sectional study found that the variables that showed positive association of breastfeeding at 6 months were Malay mothers, non working mothers, and good knowledge, had the intention to continue breastfeeding as long as possible, never felt not enough breast milk and breastfeeding due to religion. The employment factors which demonstrated a positive association with breastfeeding at 6 months were working in government sector, working half day, expressed breast milk and availability of room at workplace to express breast milk. The iv qualitative study revealed four major themes of facilitating factors. They were i) Personal factors which were perceived breast milk as the best, perceived benefits of breastfeeding especially to babies, the need of breast milk expression in workplace and strong self-motivation to express breast milk in workplace, ii) Work site support for breastfeeding in which flexible hours to express breast milk, support from employers and other employees, provision of facilities to express breast milk particularly place for expression and refrigerator. iii) Preparation for the mother's absence while at work which are learning to express breast milk and educate to feed the baby with expressed breast milk, stockpiling expressed breast milk in the refrigerator and train the baby's carer of the right way to prepare and feed the baby with expressed breast milk, iv) Baby's care taker assistance to support the mother by feeding the baby with expressed breast milk and maintaining the baby's service charged. Good knowledge on breastfeeding and perception of adequacy of breastfeeding only will increase exclusive breastfeeding practice. Education to mothers regarding the importance of exclusive breastfeeding and avoiding the practice of giving water to babies is essential. Supportive employers and a condusive working environment as well as baby's care taker assistance play an important role in sustaining breastfeeding among working mothers.